2019
DOI: 10.1002/tafs.10160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Size‐Selective Harvesting Affects Behavioral Types of a Social Fish

Abstract: In most fisheries, larger fish experience substantially higher mortality than smaller fish. Body length, life history, and behavioral traits are often correlated, such that fisheries-induced changes in size or life history can also alter

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 110 publications
(168 reference statements)
1
41
3
Order By: Relevance
“…Previous studies showed that the zebrafish selection lines differed in personality traits such as exploration, boldness and sociability (Sbragaglia, Alós, et al, ; Uusi‐Heikkilä et al, ). Our work adds to this research by showcasing that size selection has altered male aggressive behaviour during intersexual dyadic contests.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that the zebrafish selection lines differed in personality traits such as exploration, boldness and sociability (Sbragaglia, Alós, et al, ; Uusi‐Heikkilä et al, ). Our work adds to this research by showcasing that size selection has altered male aggressive behaviour during intersexual dyadic contests.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the zebrafish selection lines differed in personality traits such as exploration, boldness and sociability (Sbragaglia, Alós, et al, 2019;Uusi-Heikkilä et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations